The Big Book of Narrative Text Pagerwunung Based on CIRC Model Efforts to Improve Cursive Writing Skills - Dewi Safitri; Panca Dewi Purwati (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the design, feasibility, and effectiveness of an upright writing big book media developed to enhance the writing skills of second-grade students. The big book presents narrative texts integrating local wisdom, specifically highlighting the Pagerwunung Nature Reserve, to foster both literacy and cultural appreciation. Methodology: Employing the Research and Development (R&D) method with the Borg and Gall model, the study was conducted up to the eighth stage, focusing on feasibility and effectiveness testing due to time and cost constraints. The Cooperative Integrated Reading and Composition (CIRC) learning model was embedded into the media to strengthen collaborative reading and structured writing activities. Main Findings: The big book media design received a feasibility score of 90% from media experts and 93% from material experts, both categorized as “very feasible.” Effectiveness testing showed a significant improvement in students’ upright writing skills, supported by their increased engagement and comprehension of narrative structure. Novelty/Originality of this study: This research introduces a dual innovation: (1) integrating upright writing instruction with localized narrative content rooted in the Pagerwunung Nature Reserve, enabling students to visualize and contextualize learning through familiar cultural and environmental references; and (2) embedding the CIRC learning model into big book media, fostering cooperative literacy development while enhancing writing accuracy and fluency. By combining cultural literacy with technical writing skills, this approach not only supports academic achievement but also strengthens students’ sense of place and environmental stewardship, offering a replicable model for culturally responsive literacy instruction.